18th AIAA/CEAS Aeroacoustics Conference (33rd AIAA Aeroacoustics Conference) 2012
DOI: 10.2514/6.2012-2214
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetry and azimuthal modes in jet noise

Abstract: This paper will show that the matrix of all noise spectra radiated from a jet in a stationary condition, axisymmetric in construction and boundary conditions, has a special invariant structure which simplifies measurements and enables the total composite noise field to be expressed as a sum of mutually incoherent partial fields. Each such partial field is described in terms of an azimuthal mode with a integer wave number and polarity. The consequences of this structure include a simple explanation of the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Considering the azimuthal modes, because they are mutually incoherent, a reduced azimuthal field coherence must be due to the mixing of two or more azimuthal modes. 6,8 Several studies have calculated both correlations and coherence in the acoustic field, and have found that azimuthal coherence decreases with increasing frequency. 8,12,13,14,15 Most of the studies involving azimuthal variation in the jet noise field deal with laboratoryscale jets in an anechoic environment, where measurement apertures cover an extended portion of the jet plume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the azimuthal modes, because they are mutually incoherent, a reduced azimuthal field coherence must be due to the mixing of two or more azimuthal modes. 6,8 Several studies have calculated both correlations and coherence in the acoustic field, and have found that azimuthal coherence decreases with increasing frequency. 8,12,13,14,15 Most of the studies involving azimuthal variation in the jet noise field deal with laboratoryscale jets in an anechoic environment, where measurement apertures cover an extended portion of the jet plume.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Several studies have calculated both correlations and coherence in the acoustic field, and have found that azimuthal coherence decreases with increasing frequency. 8,12,13,14,15 Most of the studies involving azimuthal variation in the jet noise field deal with laboratoryscale jets in an anechoic environment, where measurement apertures cover an extended portion of the jet plume. The current study takes data from a measurement of a high performance military aircraft 16 and calculates the azimuthal coherence as a function of downstream distance.…”
Section: Introductionmentioning
confidence: 99%
“…Successful applications have been reported both experimentally [12,34,38] and computationally [39,40].…”
Section: Appendix B Podmentioning
confidence: 94%
“…In fact, this procedure corresponds to the one described in Ref [39]. Before going any further, note that the method described above allows reconstruction of full time histories of modal signals in the far-field making it possible to perform correlation analysis of azimuthal modes.…”
Section: Generalization Of Adt and Its Application To The Small-mentioning
confidence: 94%